2014
DOI: 10.4067/s0717-95022014000400017
|View full text |Cite
|
Sign up to set email alerts
|

Indigofera suffruticosa Mill (Fabaceae): Hepatic Responses in Mice Bearing Sarcoma 180

Abstract: SUMMARY:Indigofera suffruticosa is a plant generally used to treat infectious and inflammatory processes. This work aims to evaluate the histopathological changes in the liver tissue of mice with Sarcoma 180 after subchronic treatment with aqueous extract obtained by infusion and maceration of Indigofera suffruticosa leaves. Male mice were divided into four groups of six animals: G1, G2 and G3 patients with Sarcoma 180 and Sarcoma 180 G4 without sarcoma. G1 and G2 were treated with infusion mashing respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 6 publications
3
7
0
Order By: Relevance
“…However, hepatic tissue changes observed for the negative/saline solution control included: congested sinusoids, changes in hepatocyte cords and areas of necrosis and hemorrhage, characterizing leukocyte infiltration. Our data corroborate the results found by Silva et al (21) who demonstrated that the aqueous extract of I. suffriticosa leaves preserved the liver architecture, suggesting its use as alternative hepatoprotective agent (21) . In this study, there was reorganization of hepatocyte structural units and s inusoidal capillary cells, suggesting a possible angiogenic action in the liver of mice treated with MEIS and corroborating the pharmacological, anti-inflammatory, anticancer and antitumor properties of the extract (15,17,18) .…”
Section: In Vitro Antioxidant Activity Of Meis By Dpph Free-radical Ssupporting
confidence: 92%
See 1 more Smart Citation
“…However, hepatic tissue changes observed for the negative/saline solution control included: congested sinusoids, changes in hepatocyte cords and areas of necrosis and hemorrhage, characterizing leukocyte infiltration. Our data corroborate the results found by Silva et al (21) who demonstrated that the aqueous extract of I. suffriticosa leaves preserved the liver architecture, suggesting its use as alternative hepatoprotective agent (21) . In this study, there was reorganization of hepatocyte structural units and s inusoidal capillary cells, suggesting a possible angiogenic action in the liver of mice treated with MEIS and corroborating the pharmacological, anti-inflammatory, anticancer and antitumor properties of the extract (15,17,18) .…”
Section: In Vitro Antioxidant Activity Of Meis By Dpph Free-radical Ssupporting
confidence: 92%
“…Mice carrying sarcoma 180 had positive hepatic response to subchronic treatment with methanolic extract of I. suffruticosa leaves (20) . The structural organization of the renal tubules and hepatocyte nuclei of mice were preserved after treatment with I. suffruticosa (21,22) . The aqueous extract of I. suffruticosa leaves has low toxicity, with 98% viability of larvae (19) .…”
Section: Introductionmentioning
confidence: 99%
“…The results of the histomorphometric analysis of the area and perimeter of the hepatocyte of mice treatment with EECroton was compared with control groups without extract, but no statistical significance was observed. A similar result was found with the species I. suffruticosa belonging to the Fabaceae family (Silva et al, 2014;Lima et al, 2019). Accordingly, Silva et al (2014) demonstrated that the aqueous extract of I. suffruticosa preserved the liver architecture, and suggested its use as an alternative protective agent of the liver tissue.…”
Section: Discussionsupporting
confidence: 76%
“…The liver is an organ of importance and plays a significant role in the metabolism and detoxification of exogenous toxin and therapeutic agents (Ramachandra et al, 2007). Histological observations are important tools for the detection of morphological changes in the liver caused by bioactive compounds (Silva et al, 2014;Lima et al, 2019). From the data of that study, histological analysis was performed and it showed that there was no structural alteration in the liver tissue of mice treatment (daily doses 2000 mg/kg v.o.)…”
Section: Discussionmentioning
confidence: 99%
“…10 Mice with sarcoma 180 showed liver response after sub-chronic treatment with I. suffruticosa extract. 11 The phytochemical study of three (3) bis-indolic alkaloid fractions; Indigo and Indirubin from I. suffruticosa leaves were identified, isolated and purified. 10 However, few reports are available on the toxicological properties of I. suffruticosa, especially its genotoxic effects.…”
Section: Introductionmentioning
confidence: 99%